Doing qualitative research - Silverman, David, 1943- (Sage, 2013)
"In the fourth edition of his best-selling textbook, David Silverman provides a step-by-step guide to planning and conducting qualitative research. Using real examples from real postgraduate students, the book makes it easy to link theory to methods and shows how to move from understanding the principles of qualitative research to doing it yourself. The new edition has been fully updated and now includes: a brand new chapter on formulating a research question appropriate for qualitative research - an expanded discussion of the role of theory in research - extended discussion of case study research and the number of cases needed for effective qualitative research - further coverage of focus groups and analyzing internet data - new student examples from around the world - a new section on the common pitfalls encountered in qualitative research - an expanded companion website with more student examples and videos. Filled with exercises to test your understanding and develop your skills, as well as David's own tips for research success based on years of experience, this book is essential reading for anyone doing qualitative research."--Publisher's website.